Floppy's phonics: sounds and letters stage 3 - Hunt, Roderick; Brychta, Alex (illustrator); Debbie, Hepplewhite (phonics consultant) (Oxford University Press, Oxford, 2011)
The stories are designed to help beginner readers grasp the important link between sounds and the letters that represent them.